Integrating the Correctional System into Criminal Procedural Law : An Analytical Study on the Urgency of Legal Reform - Riki Afrizal; Tenofrimer; Diana Arma (Master of Law Program, Ekasakti University, 2025)
Corrections is a sub-system within the Indonesian criminal justice system, playing a key role in the treatment of Detainees, Children, and Inmates throughout all stages of the judicial process. However, the correctional functions as regulated under the Corrections Law have not yet been systematically integrated into the Criminal Procedure Code, which serves as the primary legal framework for criminal procedural law. This lack of integration potentially positions corrections as an institution external to the criminal justice system. This study aims to examine the current position of the correctional system within Indonesia’s criminal procedure law, assess the urgency of reforming the Criminal Procedure Code to accommodate the correctional system, and formulate an ideal integration model that aligns correctional functions within the broader criminal justice framework. This research employs a normative juridical method using statutory and conceptual approaches, and analyses them through descriptive qualitative techniques. The statutory approach focuses on an analysis of the Corrections Law, the Criminal Procedure Code, and the Draft of Criminal Procedure Code, while the conceptual approach applies legal concepts such as the correctional system and the criminal justice system. The results of this study highlight the importance of substantive reform in criminal procedural law to reflect integration and synchronisation of correctional roles in supporting the objectives of the criminal justice system. In the reform of the Criminal Procedure Code, it is necessary to regulate the position and function of corrections at the pre-adjudication, adjudication, and post-adjudication stages, particularly regarding the implementation of new types of punishment introduced in the new Criminal Code.